Pendampingan Program Perencanaan Persalinan Dan Pencegahan Komplikasi (P4K) Terhadap Pengetahuan Dan Sikap Ibu Hamil - Wulandara, Qanita; Sinar Pertiwi; Astrini Hermawati (Indonesian Journal Publisher, 2025)
The Birth Planning and Complications Prevention Program (P4K) pays special attention to birth planning and how to avoid complications associated with pregnancy, childbirth, and the puerperium. to detect the risk of complications early so that they can be treated immediately. However, pregnant women who actually take advantage of the P4K program is still low. The research method used in this research is Pre-Experimental Designs. The research design is a one-group pretest and posttest design. The population in this study were all pregnant women in the Working Area of ​​the Mangkubumi Health Center, Tasikmalaya City In December 2022, there were 684 pregnant women. The sampling technique uses quota sampling with a total sample taken of 30 respondents. The majority of pregnant women had sufficient knowledge, namely 17 pregnant women (57.00%), and 19 people (63.00%) had a positive attitude. The results of statistical tests using the Wilcoxon test showed that there was an effect of knowledge and attitudes on the implementation of the Delivery Planning and Prevention of Complications Program (P4K) assistance with a p-value of 0.000. This shows that assistance from the Planning and Prevention of Complications Program (P4K) has an effect on increasing the knowledge and attitudes of pregnant women.